1995
DOI: 10.1074/jbc.270.14.8201
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characteristics of the Candidate Prohormone Processing Proteases PC2 and PC1/3 from Bovine Adrenal Medulla Chromaffin Granules

Abstract: The prohormone-processing proteases PC1/3 and PC2 belong to the family of mammalian subtilisin-related proprotein convertases (PC) possessing homology to the yeast Kex2 protease. The presence of PC1/3 and PC2 in secretory vesicles of bovine adrenal medulla (chromaffin granules) implicates their role in the processing the precursors of enkephalin, neuropeptide Y, somatostatin, and other neuropeptides that are present in chromaffin granules. In this study, PC1/3 and PC2 were purified to apparent homogeneity from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…Notably, cleavage site studies with peptide-MCA substrates containing dibasic residue-processing sites indicated that cathepsin L prefers to cleave at the N-terminal side of dibasic residues as well as between the dibasic residues (28). In contrast, similar evaluation of PC1/3 and PC2 with dipeptide-MCA substrates showed that these PC proteases prefer to cleave at the C-terminal side of dibasic residue-processing sites (29). These data indicate that, following cathepsin L cleavage, removal of the remaining basic residue extensions at the N terminus of peptide products can be accomplished by Arg/Lys aminopeptidase activity.…”
Section: Discussionmentioning
confidence: 63%
“…Notably, cleavage site studies with peptide-MCA substrates containing dibasic residue-processing sites indicated that cathepsin L prefers to cleave at the N-terminal side of dibasic residues as well as between the dibasic residues (28). In contrast, similar evaluation of PC1/3 and PC2 with dipeptide-MCA substrates showed that these PC proteases prefer to cleave at the C-terminal side of dibasic residue-processing sites (29). These data indicate that, following cathepsin L cleavage, removal of the remaining basic residue extensions at the N terminus of peptide products can be accomplished by Arg/Lys aminopeptidase activity.…”
Section: Discussionmentioning
confidence: 63%
“…Endogenous CgA may act differently in the various tissues, depending on the presence or absence of different proteolytic mechanisms. PC1 and PC2 prohormone convertases and cathepsin L have been identified as cleavage enzymes in chromaffin vesicles (4,5); specifically, cathepsin L acts at CgA cleavage sites to synthesize Cts.…”
Section: )mentioning
confidence: 99%
“…These chromaffin granules were utilized to identify the primary proenkephalincleaving prohormone processing activity as cathepsin L using biochemistry and chemical biology approaches, as well as for studies of native in vivo prohormone convertases (38)(39)(40)(41).…”
Section: Cysteine and Serine Protease Pathways For Processing Proneurmentioning
confidence: 99%